Principal Managerial Competence and Academic Supervision on Vocational Teacher Performance - Warman Warman (PT ARRUS Intelektual Indonesia, 2022)
To reach educational success, it is crucial to have skilled teachers. The goal of this study is to illustrate how school administrators in Samarinda City's vocational high schools have increased professionalism through their administrative skills and academic oversight. Using a descriptive qualitative methodology, this study. Six informants, including two principals, two vice principals, and two teachers from two distinct vocational high schools, served as the sources for the data. In order to improve teacher professionalism, the collected data were analyzed based on the study's objectives and research questions, and categories were created using conceptualized codes of managerial competence, academic supervision of principals, and other codes of inductive and interpretive reading. The findings of this study show that the principal's managerial competence is in line with school planning in the teacher professionalism improvement program because the principal oversees facilities and infrastructure, students, curriculum, school finance, monitoring, evaluation, and reporting in addition to school organization, resource empowerment, school management, teacher and staff empowerment, and empowerment of teachers and staff. The need to address issues with learning aids, lesson plans, learning materials, classroom management, evaluation of learning results, teacher discipline, and character education implementation led the principal to introduce academic supervision. The principal attempts to develop positive relationships with teachers in order to effectively supervise them by developing a sense of kinship, talking with them and sharing information, motivating them, and setting a good example.